Seimo narių informacinė elgsena sprendimų priėmimo procese - Blagnienė, Renata (Information & Media, 2013)
Straipsnyje analizuojama Seimo narių informacinė elgsena priimant sprendimus parlamentinėje veikloje. Remiantis 2011 metų sausio–vasario mėnesiais atlikto kokybinio tyrimo duomenimis, atskleidžiami Seimo narių informacijos poreikiai, Seimo narių naudojamos informacijos ieškos strategijos, veiksniai, turintys įtakos jų informacijos ieškos elgsenai, informacijos naudojimo tikslai, Seimo narių požiūris į Seimo informacinį aprūpinimą, iškylančias problemas ir galimus jų sprendimo būdus bei informacijos poveikį priimamiems sprendimams. Duomenys surinkti naudojant asmeninio pokalbio (interviu) metodą, o duomenų analizei pasirinktas kokybinės turinio (content) analizės metodas. Reikšminiai žodžiai: sprendimų priėmimas, informacinė elgsena, informacijos ieška, informacijos poreikiai, informacinis aprūpinimas. The information behaviour of the Seimas members in decision-making process Renata Blagnienė Summary Decisions of the highest authorities condition the welfare of society. Therefore, the issue of the racionalisation of their decisions is very important. The need to reveal the grounds of the decisions of lawmakers calls for investigating their information behaviour, i.e. their behaviour in the process of information seeking, its optimization and application in the process of decision-making. The lack of research of information behaviour (from the point of view of lawmakers rather than of information providers), both in Lithuania and abroad, makes this paper innovative. In the plethora of research of information behaviour, investigations of the effect on information behaviour of parliamentarians in decision-making process are scarce. In Lithuania, no comprehensive research of the effect of information behaviour of MPs on their decisions has been conducted, with the exception of several publications about the provision of information to MPs. The subject of the research is the lack of reliable information about the infor mation needs of individual members of the Seimas and their information seeking strategies and the application of information in decision-making process. Information provision in the Seimas is organized on the basis of the traditional universal and comprehensive information provision method. More attention is given to information handling, edification of the quality of products without going into the issue of the sufficient use of prepared information and its impact on decision-making and the quality of decisions. It is difficult to evaluate the effectiveness of information services, to ensure the optimal information provision and to plan changes on the basis of assumed (therefore, not necessarily existing) model of information behaviour of the Seimas members. Understanding the factors that influence the process of decision-making and revealing the information provision problems from the perspective of lawmakers rather than of a provider of information creates prerequisites for a better and more qualified information provision. The lack of empirical research on information behaviour of the Seimas members determines the investigative nature of the present research. Attempts were made to collect as much as possible information on information needs, its seeking and use of the MPs and to reveal the factors having the greatest impact on the information seeking behaviour of the MPs. The object of research was to reveal the information behaviour of the Seimas members in the process of decision-making in their parliamentary activities. The research is focused on three major elements of information behaviour: information needs, information seeking, and information use. The aim of the research was to investigate the information behaviour of MPs, to reveal its main characteristics and to determine the variables that influence such behaviour. To achieve the aim of the research, the methods of scientific literature analysis, personal interviews, and qualitative content analysis were used. Nine respondents were interviewed during partially structural interviews which lasted 25 to 45 minutes. Transcribed texts were analyzed using the method of content analysis. The results of the research revealed the following: years of service in the Parliament and information environment have the greatest effect on the selection of information seeking strategy of MPs; the dominating information needs are those associated with lawmaking; therefore, the use of information is most intensive in this field; information seeking is realized via intermediaries; the main problem associated with information seeking is the lack of time; other problems are associated with information management, the lack of computer skills, and work organization. The respondents positively assessed the information environment of the Seimas, but certain critical remarks were expressed regarding information resources, information expedition, the quality of information services, the competencies of the staff. They suggested certain solutions to the problems.